Double transition metal / chitosan-based carbon aerogel composite material as well as preparation method and application thereof

Through the preparation of double-transition metal/chitosan-based carbon aerogel composite, the problem of insufficient catalytic capacity of zinc air batteries is solved, the stability and activity of oxygen reduction and oxygen evolution reactions are improved, and low-cost and efficient Catalytic performance, suitable for the application of zinc air batteries.

CN119324233APending Publication Date: 2025-01-17SHAANXI UNIV OF SCI & TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411432130.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The slow kinetics of zinc-air batteries are caused by weak catalytic capacity, which limits their large-scale application. The existing precious metal catalysts are costly and have poor stability, making them difficult to widely use.

Method used

Using double transition metal/chitosan-based carbon aerogel composite material, nitrogen-doped carbon aerogel is formed through freeze-drying and heat treatment to generate bimetallic organic frame materials, optimize catalytic active sites and reactant adsorption capacity, and improve catalysis performance.

Benefits of technology

It significantly improves the long-term stability of oxygen reduction and oxygen evolution reactions, improves catalytic activity and the specific surface area of ​​the material, reduces production costs, and is suitable for the application of zinc air batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses a double transition metal / chitosan-based carbon aerogel composite material and a preparation method and application thereof.The method comprises the steps that a nitrogen source and transition metal salt are added into a hydrochloric acid solution of chitosan, stirred, dissolved and evenly dispersed to prepare a mixed solution, the mixed solution is subjected to freeze drying, and the double transition metal / chitosan-based carbon aerogel composite material is obtained. Chitosan aerogel containing transition metal and a nitrogen source is prepared; the transition metal salt is any two of ferric salt, cobalt salt and nickel salt; the chitosan aerogel containing the transition metal and the nitrogen source is placed in a methanol solution of 2-methylimidazole, after vibration treatment and drying, the chitosan aerogel is placed in a nitrogen atmosphere to be subjected to heat treatment, and the double-transition-metal / chitosan-based carbon aerogel composite material is prepared. The preparation method is simple and reasonable in design, the prepared material has good specific surface area and porosity, the formed metal-nitrogen double active center effectively improves the adsorption performance of the material, and the material has good catalytic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalysis and energy storage material development, and relates to a double transition metal / chitosan-based carbon aerogel composite material and a preparation method and application thereof. Background Art

[0002] With the development of industrial civilization, human beings have an increasing demand for energy. Therefore, it is crucial to develop new sustainable green energy using advanced energy control devices such as fuel cells and metal-air batteries. In recent years, rechargeable zinc-air batteries (ZABs) have become a hot topic of research due to their high energy density and pollution-free advantages, and are considered to be one of the most promising energy storage and conversion devices. However, the slow reaction kinetics of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in zinc-air batteries seriously affect their application. Therefore, improving the kinetics of ZABs by introducing catalysts has become a research hotspot. At present, precious metal catalysts such as Pt, Ir, and Ru-based materials are the best catalysts to drive ORR and OER, but their scarce reserves, high prices, poor stability, and poisoning resistance seriously hinder the widespread application of zinc-air batteries. Therefore, it is imperative to develop low-cost, high electrochemical activity and stability non-precious metal catalysts. Among them, transition metals (Fe, Co and Ni) and their derivatives have been shown to be active centers for OER. Therefore, many transition metal-based electrocatalysts, such as layered double hydroxides (LDHs), metal / graphene, bimetallic alloys, porous metal oxides, metal phosphides, metal / porous carbon, etc., have been extensively studied. However, most of them have poor catalytic abilities, which limits the large-scale application of zinc-air batteries. Summary of the invention

[0003] In view of the problems existing in the prior art, the present invention provides a double transition metal / chitosan-based carbon aerogel composite material and a preparation method and application thereof, thereby solving the technical problem of weak catalytic ability of zinc-air batteries in the prior art.

[0004] The present invention is achieved through the following technical solutions: A method for preparing a double transition metal / chitosan-based carbon aerogel composite material comprises the following steps: S1: adding a nitrogen source and a transition metal salt to a hydrochloric acid solution of chitosan, stirring to dissolve and disperse uniformly to obtain a mixed solution, and freeze-drying the mixed solution to obtain a chitosan aerogel containing a transition metal and a nitrogen source; the transition metal salt is any two of an iron salt, a cobalt salt and a nickel salt; S2: placing the chitosan aerogel containing transition metal and nitrogen source in a methanol solution of 2-methylimidazole, shaking and drying, and then placing in a nitrogen atmosphere for heat treatment to obtain the double transition metal / chitosan-based carbon aerogel composite material.

[0005] Preferably, in step S1, the nitrogen source is at least one of urea, thiourea and melamine.

[0006] Preferably, the molar ratio of any two of the iron salt, cobalt salt and nickel salt is (1-3):(3-1).

[0007] Preferably, the molar ratio of the transition metal salt to 2-methylimidazole is (0.2-1.0):(0.1-1).

[0008] Preferably, the mass ratio of the nitrogen source to chitosan is (0.1-0.5):(1-2).

[0009] Preferably, during the freeze-drying process, the temperature is -45 to -10°C and the time is 40 to 50 hours.

[0010] Preferably, before the freeze-drying, the mixed solution is subjected to a freezing treatment, and during the freezing treatment, the temperature is -100 to -50°C and the time is 10 to 15 hours.

[0011] Preferably, in step S2, the shaking treatment is carried out at a temperature of 20-30° C. and for a time of 10-15 h.

[0012] Preferably, in step S2, during the heat treatment process, the heating rate is 5°C / min, the treatment temperature is 700-1000°C, and the treatment time is 1-5h.

[0013] A double transition metal / chitosan-based carbon aerogel composite material is prepared by the above method; the specific surface area of ​​the composite material is 300-310m 2 / g, pore size is 90~100nm.

[0014] The application of the above-mentioned double transition metal / chitosan-based carbon aerogel composite material in zinc-air batteries.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a preparation method of a double transition metal / chitosan-based carbon aerogel composite material. The composite material uses chitosan as a carbon source, and a nitrogen source is added during a freeze-drying process to form a nitrogen-doped chitosan aerogel, and then subjected to a carbonization treatment to form a nitrogen-doped carbon aerogel. The nitrogen-doped carbon aerogel material has a large specific surface area, and nitrogen doping forms catalytic active sites. In addition, during the formation of the nitrogen-doped aerogel, double transition metals and organic ligands are added, and after a vibration treatment, a double metal organic framework material is generated on the surface of the nitrogen-doped chitosan aerogel. After a heat treatment, the double metal organic framework material forms a double transition metal / carbon nanomaterial. , further improving the specific surface area of ​​carbon aerogel, and the double transition metal / carbon nanomaterial and nitrogen-doped aerogel form metal-nitrogen (MN, M refers to transition metal atom, N refers to nitrogen atom) structural sites, which serve as catalytic active centers and also improve the adhesion strength of metal particles on the surface of carbon aerogel, effectively improving the long-term stability of OER process and ORR; in this process, the use of two metals in combination causes lattice distortion due to the mismatch of lattice constants in the crystallization process, thereby changing the geometric configuration of the catalyst. This change in geometric configuration can optimize the distribution of active sites and the adsorption capacity of reactants, thereby improving catalytic activity. At the same time, the interaction between the two metals will change the electronic environment of the metal surface and promote the transfer of electrons between metals. This electronic effect can change the electronic configuration of the active metal site, making it easier to form chemical bonds with reactants, thereby accelerating the catalytic reaction. In addition, the bimetal can also improve the stability of catalytically active metals and improve their catalytic performance. The preparation method of the present invention is simple and reasonably designed. The prepared material has good specific surface area and porosity, and the formed metal-nitrogen dual active centers effectively improve the adsorption performance of the material and have good catalytic performance.

[0016] Furthermore, another inventive point of the present invention is that the molar ratio of any two of the iron salt, cobalt salt and nickel salt is (1~3):(3~1), which can effectively optimize the active site distribution of the catalyst and improve its adsorption capacity and conversion efficiency.

[0017] Further, another inventive point of the present invention is that the mass ratio of the nitrogen source to chitosan is (0.1~0.5):(1~2), and the amount of nitrogen source added directly affects the nitrogen doping degree of the chitosan-based material. The appropriate amount of nitrogen doping can significantly improve the electronic structure of the material, increase conductivity, catalytic activity and chemical stability. This ratio setting ensures that the nitrogen source can fully react with chitosan to form effective nitrogen doping, while avoiding the degradation of material performance or structural damage caused by excessive nitrogen source. Excessive nitrogen doping will cause excessive defects or stresses in the material, thereby affecting its mechanical properties and stability. This ratio allows the material to maintain good mechanical properties and stability while maintaining a high nitrogen doping level.

[0018] Furthermore, another inventive point of the present invention is that during the freeze-drying process, the temperature is -45~-10°C and the time is 40~50 h. Freeze-drying is a method for removing moisture from a material under low temperature and vacuum conditions. Within this temperature range, moisture will quickly freeze into ice crystals and directly transform from a solid state to a gas state through a sublimation process in a subsequent vacuum environment, thereby being effectively removed. This low temperature environment helps to reduce thermal degradation and structural damage of the material during the drying process and maintain the original properties of the material. The porous structure of the chitosan-based material can be well maintained during the freeze-drying process. The low temperature condition slows down the growth rate of ice crystals, reduces the damage of ice crystals to the material structure, and enables the dried material to maintain a high porosity and specific surface area. This is crucial for subsequent nitrogen doping and carbonization treatments as well as the catalytic properties of the final material. During the freeze-drying process, the pore structure of the chitosan material provides a good channel for the penetration and reaction of the nitrogen source. Appropriate temperature and time settings help the nitrogen source to be evenly distributed inside the material and to react effectively with the chitosan molecules, thereby improving the efficiency of nitrogen doping. In addition, low temperature conditions also help reduce the volatilization and loss of nitrogen sources during the reaction process. The freeze-dried chitosan material has a lower water content and higher porosity, which allows heat to be transferred more evenly to the interior of the material during the subsequent carbonization process, reducing the risk of material burning or structural damage due to local overheating. At the same time, higher porosity helps the gas generated during the carbonization process to be discharged smoothly, avoiding defects such as bubbles or cracks in the material. By optimizing the temperature and time settings of the freeze-drying process, chitosan-based carbon aerogel composites with excellent performance can be prepared.

[0019] Furthermore, another inventive point of the present invention is that before the freeze-drying is performed, the mixed solution is subjected to a freezing treatment. During the freezing treatment, the temperature is -100~-50 ℃ and the time is 10~15 h. First, at such a low temperature, the water in the solution will quickly and evenly freeze into ice crystals. This rapid and uniform formation of ice crystals helps to reduce the damage of ice crystals to the material structure because the growth rate of ice crystals is slower and the distribution is more uniform. At the same time, it also provides a better basis for the subsequent sublimation process, so that water can be removed more effectively during the freeze-drying process. Low-temperature freezing treatment helps to reduce the damage to the material structure caused by the volume expansion caused by the freezing of water. At higher temperatures, the volume of water will increase significantly when it freezes, which may cause stress or cracks inside the material. At low temperatures of -100 ℃ to -50 ℃, the volume expansion effect of water freezing is greatly weakened, thereby protecting the original structure of the material. The mixed solution that has been fully frozen can sublimate and remove water faster during the freeze-drying process because the ice crystals have been stably formed and evenly distributed. Therefore, in a vacuum environment, these ice crystals can be more efficiently converted into gaseous water molecules through the sublimation process and discharged from the system. This shortens the drying time and improves production efficiency. The ice crystals formed during the freezing process will leave pores after sublimation. These pores constitute the porous structure of the material. At low temperatures of -100 ℃ to -50 ℃, the shape and distribution of the ice crystals are more regular, so the pore structure left after sublimation is also more uniform and stable. This porous structure is beneficial for improving the specific surface area, adsorption performance and catalytic activity of the material.

[0020] Furthermore, another inventive point of the present invention is that in step S2, the temperature of the oscillation treatment is 20-30°C and the time is 10-15 h, and the oscillation treatment can effectively promote the mixing uniformity of the components in the mixed solution. At an appropriate temperature, the movement speed of molecules and ions is moderate, which is conducive to their interaction and uniform distribution. Long-term oscillation can ensure that the components in the solution reach a fully mixed state and avoid the phenomenon of excessive or low local concentration. The oscillation treatment can also significantly improve the efficiency of the reaction. Through continuous oscillation, the contact area between the reactants increases, and the collision opportunities between the reactant molecules increase, thereby accelerating the rate of the chemical reaction. In addition, the oscillation treatment also provides a good foundation for subsequent processing steps (such as freezing treatment, freeze drying, etc.). By ensuring the uniformity and stability of the mixed solution, the subsequent processing process can be made smoother and more efficient. For example, during the freezing treatment process, a uniform mixed solution can form a more regular and stable ice crystal structure; during the freeze drying process, it can more effectively remove moisture and retain the original structure of the material.

[0021] Furthermore, another inventive point of the present invention is that in step S2, during the heat treatment process, the heating rate is 5 °C / min, the treatment temperature is 700~1000 °C, and the time is 1~5 h. The heating rate of 5 °C / min is a relatively slow heating process, which helps to reduce the thermal stress generated by the rapid temperature change in the material during the heating process. Thermal stress may cause cracks or structural damage inside the material, while the slower heating rate allows the material to gradually adapt to the temperature change, thereby maintaining its structural integrity. The treatment temperature is set in the range of 700~1000 °C, which is the ideal temperature range for pyrolysis and carbonization reactions of organic substances such as chitosan. Within this temperature range, organic molecules will undergo reactions such as fracture, recombination and cross-linking to form a carbon material with a stable structure and excellent performance. At the same time, high temperature also helps to remove volatile components and impurities in the material, further improving the purity of the material. The setting of the treatment time allows for fine control of the degree of carbonization. A shorter treatment time may result in incomplete carbonization, while a longer treatment time may cause the material to be over-carbonized and lose certain properties. By adjusting the treatment time, the degree of carbonization can be optimized while maintaining the structural stability of the material, thereby obtaining a material with optimal performance. The heat treatment process can also significantly improve the thermal stability, mechanical strength, electrical conductivity, and catalytic activity of the material. At high temperatures, the chemical bonds within the material are strengthened, forming a more stable structure; at the same time, the pores and defects generated during the carbonization process also provide more active sites for the material, which is conducive to improving its catalytic activity and adsorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 The scanning electron microscope images of the double transition metal / chitosan-based carbon aerogel composite material (NC-Fe1Co3) prepared in Example 1 of the present invention, wherein (a) to (d) are different magnification scales; Figure 2 The specific surface area test results of the double transition metal / chitosan-based carbon aerogel composite material (NC-Fe1Co3) prepared in Example 1 of the present invention; Figure 3 The pore size distribution test results of the double transition metal / chitosan-based carbon aerogel composite material (NC-Fe1Co3) prepared in Example 1 of the present invention; Figure 4The double transition metal / chitosan-based carbon aerogel composite material (NC-Fe x Co y ) Linear Sweep Voltammetry (LSV) scanning curve in 1M KOH solution; Figure 5 Transmission electron microscopy image of the double transition metal / chitosan-based carbon aerogel composite material (NC-Fe1Co3) prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0025] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0026] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0027] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0028] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0029] The invention discloses a method for preparing a chitosan-based carbon aerogel-anchored iron-cobalt nano-alloy electrocatalyst, comprising the following steps: 1) 0.1-0.5 g of chitosan is dissolved in 10-20 mL of 0.1 M hydrochloric acid solution; 1-2 g of nitrogen source and a certain amount of transition metal salt are added to the chitosan hydrochloric acid solution, wherein the transition metal salt is any two of iron salt, cobalt salt and nickel salt, and the mixture is poured into a mold after stirring for 1-3 h, and then frozen at -100°C to -50°C for 10-15 h, and then freeze-dried at -45°C to -10°C for 40-50 h using a freeze dryer to obtain carbon aerogel; Wherein, the nitrogen source is at least one of urea, thiourea and melamine.

[0030] The molar ratio of any two of the iron salt, cobalt salt and nickel salt is (1-3):(3-1).

[0031] 2) The carbon aerogel is immersed in a methanol solution of 2-methylimidazole, placed in a shaker at 20-30°C for 10-15 hours, and the shaken product is placed in an oven to dry, thereby obtaining a carbon aerogel loaded with an organic metal framework material.

[0032] Wherein, the molar ratio of the transition metal salt to 2-methylimidazole is (0.2-1.0):(0.1-1).

[0033] 3) placing the carbon aerogel loaded with the organic metal framework material in flowing N2 for heat treatment, wherein the heating rate is 5°C / min, the treatment temperature is 700-1000°C, and the treatment time is 1-5h to obtain a double transition metal / chitosan-based carbon aerogel composite material.

[0034] The purpose of the present invention is to prepare chitosan-based carbon aerogel anchored NC-double transition metal catalyst by immersing chitosan aerogel containing double transition metal in a methanol solution of 2-methylimidazole and pyrolyzing it, wherein the NC-double transition metal catalyst is a product of heat treatment of an organic metal framework material, and the product is a hollow shell material, and the shell is a composite material of nitrogen-doped carbon and double transition metal. By regulating the ratio of transition metals and optimizing the preparation steps, a carbon aerogel anchored with double transition metals and having a rich pore structure is prepared.

[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0036] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0037] Example 1 A method for preparing a chitosan-based carbon aerogel anchored iron-cobalt nano alloy electrocatalyst comprises the following steps: a. Weigh 0.3 g chitosan and dissolve it in 15 mL 0.1 M hydrochloric acid solution to form a white transparent chitosan solution.

[0038] b. Add 1.2 g urea and 2 mL of a mixed solution of Fe(NO3)3∙9H2O and Co(NO3)2∙6H2O in a molar ratio of 1:3. Stir for 2 h to allow the mixture to fully dissolve and then pour the solution into a 1×1×1 cm 3 The obtained carbon aerogel was soaked in 50mL of 0.1 M 2-methylimidazole methanol solution and placed in a shaker at a constant temperature of 25°C for 12 hours. The soaked aerogel was placed in an oven at 80°C for drying. c. The chitosan aerogel was pyrolyzed in flowing N2 at a rate of 5 °C / min to the target temperature for 3 h to obtain carbon aerogel NC-Fe1Co3, where the subscript of Fe1Co3 represents the molar ratio of the two metals.

[0039] Example 2 A method for preparing a chitosan-based carbon aerogel anchored iron-cobalt nano alloy electrocatalyst comprises the following steps: a. Weigh 0.3 g chitosan and dissolve it in 15 mL 0.1 M hydrochloric acid solution to form a white transparent chitosan solution.

[0040] b. Add 1.2 g urea and 2 mL of a 1:1 molar ratio mixed solution of Fe(NO3)3∙9H2O and Co(NO3)2∙6H2O. Stir for 2 h to allow the mixture to fully dissolve and then pour the solution into a 1×1×1 cm 3The obtained carbon aerogel was soaked in 50mL of 0.1M methanol solution of 2-methylimidazole and placed in a shaker at a constant temperature of 25℃ for 12h. The soaked aerogel was placed in an oven at 80℃ for drying.

[0041] c. The chitosan aerogel was pyrolyzed in flowing N2 at a rate of 5 °C / min to the target temperature for 3 h to obtain carbon aerogel NC-Fe1Co1.

[0042] Example 3 A method for preparing a chitosan-based carbon aerogel anchored iron-cobalt nano alloy electrocatalyst comprises the following steps: a. Weigh 0.3 g chitosan and dissolve it in 15 mL 0.1 M hydrochloric acid solution to form a white transparent chitosan solution.

[0043] b. Add 1.2 g urea and 2 mL of a mixed solution of Fe(NO3)3∙9H2O and Co(NO3)2∙6H2O in a molar ratio of 3:1. Stir for 2 h to allow the mixture to fully dissolve and then pour the solution into a 1×1×1 cm 3 The obtained carbon aerogel was soaked in 50mL of 0.1M methanol solution of 2-methylimidazole and placed in a shaker at a constant temperature of 25°C for 12 hours. The soaked aerogel was placed in an oven at 80°C for drying. c. The chitosan aerogel was pyrolyzed in flowing N2 at a rate of 5°C / min to the target temperature for 3 h to obtain carbon aerogel NC-Fe3Co1.

[0044] Figure 1 This is a scanning electron microscope image of the double transition metal / chitosan-based carbon aerogel composite material (NC-Fe1Co3) prepared in Example 1 of the present invention, wherein: Figure 1 (a) illustrates the formation of carbon aerogel structure. Figure 1 (b) shows the carbon aerogel formed by individual carbon nanosheets. Figure 1 (c) It shows that the surface of carbon nanosheets is rough and contains many pores. Figure 1 (d) It shows that particles formed by carbonization of metal organic frameworks grow on the surface of carbon nanosheets.

[0045] Figure 2The specific surface area test results of the double transition metal / chitosan-based carbon aerogel composite material (NC-Fe1Co3) prepared in Example 1 of the present invention are shown in the figure. As can be seen from the figure, the specific surface area of ​​the composite material prepared in this example is 304m 2 / g, which effectively increases the number of catalytic active sites and promotes the adsorption and conversion of reactants. At the same time, it makes the diffusion and mass transfer of reactants more effective on the surface of the material, making it easier for reactants to approach the active sites, further improving the rate and efficiency of the catalytic reaction.

[0046] Figure 3 The pore size distribution test results of the double transition metal / chitosan-based carbon aerogel composite material (NC-Fe1Co3) prepared in Example 1 of the present invention are shown. As can be seen from the figure, the pore size of the composite material prepared in this example is mainly 92 nm, which belongs to the mesoporous range. Pores of this size are conducive to the diffusion and mass transfer of reactants inside the material. A larger pore size can reduce mass transfer resistance and make it easier for reactants to approach catalytic active sites, thereby increasing the rate of the catalytic reaction. At the same time, it can also ensure that the catalytic active sites are fully exposed, avoiding the problem of active site blockage or difficulty in access due to too small pore size.

[0047] Figure 4 The double transition metal / chitosan-based carbon aerogel composite material (NC-Fe x Co y ) in 1M KOH solution. It can be seen from the figure that the starting potential and half-wave potential of the double transition metal / chitosan-based carbon aerogel composite material prepared in the present invention are higher than those of Pt / C+RuO2, among which the starting potential and half-wave potential of NC-Fe1Co1 are 0.99 V and 0.86 V, respectively, the starting potential and half-wave potential of NC-Fe1Co3 are 1.01 V and 0.88 V, respectively, the starting potential and half-wave potential of NC-Fe3Co1 are 0.96 V and 0.85 V, respectively, and the starting potential and half-wave potential of Pt / C+RuO2 are 0.95V and 0.84 V, respectively, indicating that the double transition metal / chitosan-based carbon aerogel composite material prepared in the present invention has good oxygen reduction performance; and when the molar ratio of iron atoms to cobalt atoms is 1:3, it shows a higher starting potential and half-wave potential (1.01V and 0.88 V), are higher than NC-Fe1Co1 and NC-Fe3Co1, indicating that the addition ratio of Fe and Co has a significant effect on the oxygen reduction performance of the catalyst.

[0048] Figure 5The transmission electron microscope image of the double transition metal / chitosan-based carbon aerogel composite material (NC-Fe1Co3) prepared in Example 1 of the present invention shows that the (100) crystal plane of the CoFe alloy (JCPDS No. 44-1433) can be clearly observed.

[0049] Example 4 A method for preparing a chitosan-based carbon aerogel anchored iron-cobalt nano alloy electrocatalyst comprises the following steps: 1) Take 0.1 g of chitosan and dissolve it in 10 mL of 0.1 M hydrochloric acid solution; add 1 g of urea and a certain amount of transition metal salt to the chitosan hydrochloric acid solution, wherein the transition metal salt is a mixture of iron salt and cobalt salt with a molar ratio of 1:3, stir for 1 hour, pour into a mold, freeze at -50°C for 10 hours, and then freeze-dry at -10°C for 50 hours in a freeze dryer to obtain carbon aerogel; any two of the iron salt, cobalt salt and nickel salt.

[0050] 2) The carbon aerogel was immersed in a methanol solution of 2-methylimidazole, placed in a shaker at 20°C for 15 hours, and the shaken product was placed in an oven to dry, thereby obtaining a carbon aerogel loaded with an organic metal framework material.

[0051] Wherein, the molar ratio of the transition metal salt to 2-methylimidazole is 0.2:0.1.

[0052] 3) placing the carbon aerogel loaded with the organic metal framework material in flowing N2 for heat treatment, during which the heating rate is 5°C / min, the treatment temperature is 700°C, and the treatment time is 5h to obtain a double transition metal / chitosan-based carbon aerogel composite material.

[0053] The specific surface area of ​​the composite material prepared in this embodiment is 300m 2 / g, pore size is 100nm.

[0054] Example 5 A method for preparing a chitosan-based carbon aerogel anchored iron-cobalt nano alloy electrocatalyst comprises the following steps: 1) 0.5 g of chitosan was dissolved in 20 mL of 0.1 M hydrochloric acid solution; 2 g of thiourea and a certain amount of transition metal salt were added to the chitosan hydrochloric acid solution, wherein the transition metal salt was a mixture of cobalt salt and nickel salt in a molar ratio of 3:1, stirred for 3 h, poured into a mold, frozen at -100 °C for 15 h, and then freeze-dried at -45 °C for 40 h using a freeze dryer to obtain carbon aerogel; 2) The carbon aerogel was immersed in a methanol solution of 2-methylimidazole, placed in a shaker at 30°C for 10 h, and the shaken product was placed in an oven to dry, thereby obtaining a carbon aerogel loaded with an organic metal framework material.

[0055] Wherein, the molar ratio of the transition metal salt to 2-methylimidazole is 1.0:1.

[0056] 3) placing the carbon aerogel loaded with the organic metal framework material in flowing N2 for heat treatment, wherein the heating rate is 5°C / min, the treatment temperature is 1000°C, and the treatment time is 1 h, to obtain a double transition metal / chitosan-based carbon aerogel composite material.

[0057] The specific surface area of ​​the composite material prepared in this embodiment is 310m 2 / g, pore size is 90nm.

[0058] Example 6 A method for preparing a chitosan-based carbon aerogel anchored iron-cobalt nano alloy electrocatalyst comprises the following steps: 1) 0.3 g of chitosan was dissolved in 15 mL of 0.1 M hydrochloric acid solution; 1.5 g of melamine and a certain amount of transition metal salt were added to the chitosan hydrochloric acid solution, wherein the transition metal salt was a mixture of iron salt and nickel salt in a molar ratio of 1:1, stirred for 2 h, poured into a mold, frozen at -80 ° C for 12 h, and then freeze-dried at -30 ° C for 45 h in a freeze dryer to obtain carbon aerogel; 2) Soaking the carbon aerogel in a methanol solution of 2-methylimidazole, shaking it in a shaker at 25°C for 12 hours, and drying the shaken product in an oven to obtain a carbon aerogel loaded with an organic metal framework material, wherein the molar ratio of the transition metal salt to 2-methylimidazole is 0.5:0.6.

[0059] 3) placing the carbon aerogel loaded with the organic metal framework material in flowing N2 for heat treatment, wherein the heating rate is 5°C / min, the treatment temperature is 800°C, and the treatment time is 3 h, to obtain a double transition metal / chitosan-based carbon aerogel composite material.

[0060] The specific surface area of ​​the composite material prepared in this embodiment is 305m 2 / g, pore size is 95nm.

[0061] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a double transition metal / chitosan-based carbon aerogel composite material, characterized in that: The following steps are involved: S1: adding a nitrogen source and a transition metal salt to a hydrochloric acid solution of chitosan, stirring to dissolve and disperse uniformly to obtain a mixed solution, and freeze-drying the mixed solution to obtain a chitosan aerogel containing a transition metal and a nitrogen source; the transition metal salt is any two of an iron salt, a cobalt salt and a nickel salt; S2: placing the chitosan aerogel containing transition metal and nitrogen source in a methanol solution of 2-methylimidazole, shaking and drying, and then placing in a nitrogen atmosphere for heat treatment to obtain the double transition metal / chitosan-based carbon aerogel composite material.

2. The method for preparing a double transition metal / chitosan-based carbon aerogel composite material according to claim 1, characterized in that: In step S1, the nitrogen source is at least one of urea, thiourea and melamine.

3. The method for preparing a double transition metal / chitosan-based carbon aerogel composite material according to claim 1, characterized in that: The molar ratio of any two of the iron salt, cobalt salt and nickel salt is (1-3):(3-1).

4. The method for preparing a double transition metal / chitosan-based carbon aerogel composite material according to claim 1, characterized in that: The molar ratio of the transition metal salt to 2-methylimidazole is (0.2-1.0):(0.1-1); the mass ratio of the nitrogen source to chitosan is (0.1-0.5):(1-2).

5. The method for preparing a double transition metal / chitosan-based carbon aerogel composite material according to claim 1, characterized in that: During the freeze-drying process, the temperature is -45 to -10°C and the time is 40 to 50 hours.

6. The method for preparing a double transition metal / chitosan-based carbon aerogel composite material according to claim 1, characterized in that: Before the freeze-drying, the mixed solution is subjected to a freezing treatment, during which the temperature is -100 to -50°C and the time is 10 to 15 hours.

7. The method for preparing a double transition metal / chitosan-based carbon aerogel composite material according to claim 1, characterized in that: In step S2, the shaking treatment is performed at a temperature of 20-30°C for 10-15 hours.

8. The method for preparing a double transition metal / chitosan-based carbon aerogel composite material according to claim 1, characterized in that: In step S2, during the heat treatment process, the heating rate is 5°C / min, the treatment temperature is 700-1000°C, and the treatment time is 1-5h.

9. A double transition metal / chitosan-based carbon aerogel composite material, characterized in that: The composite material is prepared by the method according to any one of claims 1 to 8; the specific surface area of ​​the composite material is 300 to 310 m 2 / g, pore size is 90~100nm.

10. Use of the double transition metal / chitosan-based carbon aerogel composite material as claimed in claim 9 in a zinc-air battery.

Citation Information

Cited By

  • Bi-crosslinked carbon aerogel as well as preparation method and application thereof

    CN121266558A

  • Bimetal nitride catalyst as well as preparation method and application thereof

    CN122006781A